(3GdCLhHI GdeQVjI Yf CFeI GdabgGA hGdUhajIs - (3YHO GdhgGH Hf CMeO Hf Ydj GdnMnfaj, fSHg Edi eMeO GHf GdMfajI, GdTYQGfj, CHh eMeO , J (B973 (3g`s
(3ChdgG (B:s
(3GdMeO ddg Pi GdaVd hGdLhO GdPi EUWai ef YHGOg CbhGekG s
(3BNQgG (B:s
(3aEf de jcf Ydjg TF ef eXGde GdYHGO LGR GdUQGW cdg Edi GdLfI GfJgi cJGH GdCLhHI GdeQVjI Yf CFeI GdabgGA hGdUhajI s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B180s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3GdJUha hGdBOGH GdTQYjIs